Extract of Allium Chinense G. Don, a Medicinal Plant, Ameliorates Myocardial Ischemia–Reperfusion Injury by Inhibiting Platelet Activation - Siyuan Liu; Huaxiang Wang; Min Wang; Zhihui Wang; Na Li; Jianyong Si; Jingxue Ye (Current Issues in Molecular Biology, 2025)
Allium chinense G. Don is valued for its edible and medicinal qualities. It has been reported that Allium chinense has the potential to inhibit platelet activation, but its mechanism of action is unknown, which needs to be further explored. This study investigates the anti-myocardial ischemia–reperfusion (I/R) injury potential of Allium chinense from the perspective of platelet activation, focusing on its chemical composition and underlying mechanisms of action. A combination of transcriptome sequencing, molecular docking, and experimental validation was employed in our study. The antiplatelet active fraction MT-95ET of Allium chinense was screened by the ADP-induced platelet aggregation model in vitro. In vivo experiments demonstrated that MT-95ET can reduce the myocardial injury of I/R rats and inhibit I/R-induced platelet activation, adhesion, and aggregation. UHPLC-Q-Orbitrap-MS/MS was used to identify 13 compounds from MT-95ET. Transcriptome sequencing and molecular docking identified aerobic glycolysis key checkpoints PDK1 and PKM2 as key targets, with Sarsasapogenin and Hecogenin exhibiting strong binding affinities to these proteins. Western blot analysis further validated that MT-95ET downregulated PKM2 and PDK1, indicating a possible mechanism for its antiplatelet effects and anti-myocardial I/R injury.